THE PERFORMANCE OF CIVIC EDUCATION TEACHER ON PLANNING AND LEARNING PROCESS IN JUNIOR HIGH SCHOOL 1 CAMPAKA KABUPATEN PURWAKARTA - Dadang Sundawa, Nur Endah Apriliyani Sapriya (Department of Civic Education, 2014)
The result of research indicates that (1) the Civic Education’s teacher in the activity of learning plan can afford to develop the basic design of curriculum, to apply the learning load, to arrange the academic calendar, to develop the syllabus, as well as to arrange and develop RPP as a guideline in the learning process structured based on the competency that must be achieved by the educated participants; (2) the Civic Education’s teacher in applying the learning plan in the learning process has mastered the standard of Civic Education learning process in the classroom, be able to develop the Civic Education learning material creatively, be able to manage the classroom in the Civic Education learning, and the teacher has mastered the standard of educational evaluation in the Civic Education learning; (3) the Civic Education’s teacher in evaluating the learning process and result has implemented the authentic assesment by using various evaluating manners/techniques, implementing authentic assesment by regarding the cognitive, affective, and psychomotor aspects, as well as the result of evaluation analyzed by the teacher as a feedback material for the students and teacher, and/or for determining the student’s achievement.Keywoard: Teacher’s Performance, Planning and Process of LearningABSTRAK